UJI TARIK HIDRODINAMIKMODEL KAPAL BERSAYAP WiSE DENGAN LAMBUNG DASAR BERSTEP - Iskendar, Iskendar; Jamaludin, Andi; Indiyono, Paulus (Jurnal Sains dan Teknologi Indonesia, 2010)
This paper describes hydrodynamic model tests of Wing in Surface Effect (WiSE) Craft. These craft was fitted with stephull form in different location on longitudinal flat bottom (stepedhull planning craft) to determine the influences of sticking and porpoising motion performances. These motions are usually occured when the craft start to take-off from water surfaces. The test models with scale of 1 : 7 were comprised of 4 (four) stephull models and 1 (one) non-stephull model as a comparative study. The hydrodynamic tests were performed with craft speed of 16 – 32 knots (prototype values) in Towing Tank at UPT. Balai Pengkajian dan Penelitian Hidrodinamika (BPPH), BPPT, Surabaya. The resistance (drag) was measured by dynamo meter and the trim of model (draft changing at fore and aft of model due to model speed) was measured by trim meter. By knowing the value of model trim, the wetted surface area can be determined. Then, the lift forces were calculated based on these measured values. The model test results were presented on tables and curves. Test results show that models with step located far away from center of gravity of the WiSE craft tend to porpoising and sticking condition, except if the step location on the below of these center of gravity. While model without step tends to sticking conditions.